The Social Construction of Technology for the Use of CHATGPT in Indonesia - Wibowo, Tangguh Okta (ETTISAL : Journal of Communication, 2024)
The purpose of this study is to map the vulnerable issue about ChatGPT in academic field. This study seeks to understand the role of online media channels in mediating the understanding behind the use of ChatGPT in Indonesia. This is because the media also constructs how new technology is used, so that the use of technology is not neutral or taken for granted according to what users want. Thus, mapping the information constructed by the media is important to locate in the context of the use of ChatGPT in Indonesia. The main research question of this paper is how does the media construct the discourse related to how ChatGPT should be used? This study tries to fill the knowledge gap over the use of ChatGPT through the social construction of technology (SCOT) approach. This study uses literature review as a method to understand the discourse about the use of ChatGPT through the existence of "relevant social groups". The result shows that online media channels not only act as producers of information, but also act as groups that construct a discourse behind the presence of ChatGPT. This study expands by analyzing the reporting or production of information about ChatGPT through online media channels in Indonesia by identifying three main themes namely context, navigation, and imagination. From the results of this study, it can be concluded that the use of ChatGPT constructs a discourse that triggers concerns regarding its misuse as misleading technology if there is no regulation surrounding it. Therefore, strict laws, regulations, and supervision need to be implemented to ensure the optimal use of ChatGPT and in accordance with the desired goals in related fields.